Exploring Ethnomathematics in a Malay Traditional House and Architecture on Meranti Island as a Geometry Learning Resource for Elementary School - Atik Luthfia Cahyani; Putra, Zetra Hainul; Witri, Gustimal; Ahmad, Sagheer (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2025)
Traditional architecture often reflects the cultural values, local wisdom, and mathematical thinking of a community. In Meranti Island, traditional Malay houses contain rich geometric elements that have yet to be fully explored in the context of mathematics education. This research aims to investigate the traditional Malay house and architectural designs in Meranti Island a culturally relevant resource for teaching geometry in elementary schools. This study lies in integrating ethnomathematics into the elementary geometry curriculum by utilizing local architectural heritage, which has received limited academic attention. An ethnographic approach was employed to gain a deep understanding of the cultural and mathematical aspects embedded in the traditional architecture. This method was chosen as it allows researchers to capture the contextual meaning and lived experiences of the community through interviews, observations, documentation, and field notes. The findings reveal that traditional Malay houses in Meranti Island incorporate a variety of geometric concepts. Flat shapes identified include squares, rectangles, triangles, rhombuses, parallelograms, and trapezoids, while solid shapes include cubes, cuboids, cylinders, and triangular prisms. These findings demonstrate that traditional architectural elements can serve as meaningful and contextual learning materials for geometry instruction. The practical implication of this study is the development of culturally responsive teaching strategies that connect students' local environments with mathematical concepts. This approach not only enhances students’ understanding of geometry but also fosters appreciation for local culture and identity through mathematics learning.